Pola Interaksi antara Guru Pendidikan Agama Islam dan Siswa dalam Meningkatkan Kedisiplinan Siswa di SMP Negeri 15 Padang - Dinda Septiarini; Wirdati Wirdati (ISLAMIKA, 2022)
This research problem is motivated by the lack of student discipline at school, seeing this problem the emergence of a pattern of interaction between PAI teachers and students in improving student discipline at SMP Negeri 15 Padang. This study aims to determine how the pattern of interaction between Islamic religious education teachers and students in improving student discipline at SMP Negeri 15 Padang. This type of qualitative research is descriptive. The results of the study revealed that first, the pattern of one-way interaction between PAI teachers and students in improving discipline, namely 1) by conveying rules in compulsory school activities, 2) conveying rules before learning. Second, the pattern of two-way interaction between PAI teachers and students in improving discipline, namely 1) socializing the rules to students (face to face), 2) calling students by motivating and advising. Third, the pattern of multi-way interaction between PAI teachers and students in improving student discipline, namely 1) socializing the rules to students and parents 2) calling students' parents.